2016
DOI: 10.14474/ptrs.2016.5.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sit-to-stand imagery group training on balance performance in individuals with chronic hemiparetic stroke: a randomized control trial

Abstract: Objective: To evaluate the effects of sit-to-stand (STS) imagery group training (IGT) on STS movement and balance performance for chronic hemiparetic stroke. Design: Randomized controlled trial. Methods: A total of 30 people with chronic hemiparetic stroke (15 for STS-IGT group and 15 for control) were recruited in this study. The STS-IGT group participated in a videotape-based STS-IGT for 30 minutes a day, five days a week for six weeks, while the control group watched a documentary on television for the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In addition, a significant increase in extension angular velocity after MI was seen, which has been previously suggested to be a measure of improved quality of movement (Richards et al 2003), although it should be noted the percentage increase was only 4%. However, this supports the concept of changes in motor performance as a consequence of mental training in healthy subjects (Gentili et al 2010;Gentili & Papaxanthis 2015;Luger et al 2019), and in individuals with chronic hemiparetic stroke for both simple reaching tasks without grasping and sit to stand tasks (Guttman et al 2012;Lee et al 2016).…”
Section: Discussionsupporting
confidence: 76%
“…In addition, a significant increase in extension angular velocity after MI was seen, which has been previously suggested to be a measure of improved quality of movement (Richards et al 2003), although it should be noted the percentage increase was only 4%. However, this supports the concept of changes in motor performance as a consequence of mental training in healthy subjects (Gentili et al 2010;Gentili & Papaxanthis 2015;Luger et al 2019), and in individuals with chronic hemiparetic stroke for both simple reaching tasks without grasping and sit to stand tasks (Guttman et al 2012;Lee et al 2016).…”
Section: Discussionsupporting
confidence: 76%
“…Intervention methods for balance improvement in stroke survivors include visual feedback [12], imagery training [13], robot-assisted gait training [14], muscle strength training [15], whole-body vibration training [16], electrical nerve stimulation [17], and virtual reality [18]. Virtual reality training is often used to rehabilitate stroke survivors who have limited physical activity or cannot complete leisure activities in a real environment due to limited environmental and physical disability.…”
Section: Introductionmentioning
confidence: 99%
“…Following a stroke, patients rise from a chair by bearing more weight on the non-paretic foot from phases 1 to 4, although they improve and perform symmetric STS through visual feedback [3], imagery group training [11], and by altering the foot positions [9]. Bohannon et al [12] reported that there is at least a 50% error difference between the perceived body weight born on the foot and the practical distribution in healthy people.…”
Section: Introductionmentioning
confidence: 99%